AfriKaleidoskop meets ARTESüdafrikas Weg aus der Apartheid: Discussion (Afrikaleidoskop meets ARTE, 2025)
On 8th May 2025 the Cluster of Excellence hosted another event within the frame of our well-received cinema lecture series AfriKaleidoskop meets ARTE at Kulturhaus Neuneinhalb in Bayreuth. It was an exclusive preview screening of ARTE of the first part of the three-part documentary series Südafrikas Weg aus der Apartheid (in German, translated from the original “Free at last: Unsolved stories of Apartheid”), a coproduction of the renowned female South African film maker and actress Xoliswa Sithole (winner of BAFTA prices), and the Dutch investigative journalists Misha Wessel and Thomas Blom. Teil 1: Suche nach Antworten (in German with English subtitles) was screened and followed by a panel discussion with Cluster scholar Patricia Pinky Ndlovu-Gatsheni, the filmmaker Thomas Blom and a subsequent Q&A session with the audience. This part of the event was recorded and made available here on YouTube and in the event media hub of ARTE.